Effects of the Social Media in the Marketing of Political Candidates in Nigeria - Victor O., Okolo; Ikechukwu A., Ugonna; Gerald N and Obikeze Chinedum O., Nebo (British Journal of Marketing Studies, 2017)
Social media are new information network and information technology using a form of communication utilizing interactive and user-produced content, and interpersonal relationships are created and maintained. More recently, the prominence of social media has been particularly highlighted in politics, given the fact that the use of social networking sites (Facebook) and micro blogging services (Twitter) are believed to have the potential of positively influencing political participation. The use of social media platforms are important tools within political communication campaigns to secure victory and encourage interaction between political parties/candidates and voters, and most times to portray positive image of the political candidates. Incidentally, in Nigeria, the everyday use of social media by politicians, and the manner in which the user-citizen interacts with the social network sites/pages of politicians has received rather less attention. Essentially, politicians expect the communication relationship to be positive and of benefit to them, thus, political gladiators of all shades of opinions, ideologies, intents and goals use the media with the belief that political communication through them might exert pressure or influence on people’s perception and behaviours and this has given rise to both ethical and unethical political communication and desperate political contenders manifesting bad governance, thereby, leading to social and economic infrastructural neglect and security of lives and property. The main objective of the study is to determine the effect of social media in projecting the image of political candidate in Nigeria. The research adopted the descriptive survey design. The population of the study comprises of the masses [i.e. the electorate] and the members of political parties (political candidates) in Nigeria who uses social media. Primary data and secondary sources of information were employed. Data were tested using simple percentages, Pearson Moment Correlation Coefficient and Regression analyses at 0.05 level of significance. Findings from the study showed that: There is a significant positive relationship between usage of Facebook as an awareness social media tool and projection of a political candidates’ image in Nigeria(r = 0.764; F = 418.677; p < 0.05). Blogging as a credible social media tool to a large extent influences image of a political candidate in Nigeria (r = 0.728; p<0.05). It was concluded that social media serve as credible tools and are capable of influencing the image of political candidates in Nigeria. The study therefore recommended that political candidates should carefully plan and execute communication strategies using various social media tools, so as to fully enjoy the inherent benefits of the social media tools (i.e credibility and awareness).